Case Report: Meningitis Streptococcus suis Presented with spondylodiscitis in Bali - Adnyana, I Made Oka; Susilawathi, Ni Made; Indradewi, Anak Agung Ayu Suryapraba; Yaputra, Faldi; Asih, Made Widhi; Budayanti, Ni Nyoman Sri; Maliawan, Sri (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Human infection of Streptococcus suis in Indonesia was increasing in the following years. Many cases presented with meningitis and sepsis, but in the current case, we presented a rare case of meningitis S. suis infection with spondylodiscitis. CASE REPORT: A 60-year-old man, Balinese, presented with the 3-day onset of fever, headache, and nausea. Three-hour before admission, he became agitated and decreased of consciousness. He had a history of pork consumption 4 days before admission. He was subsequently diagnosed with acute bacterial meningitis and sensorineural hearing impairment. In the next 2 weeks, he developed low back pain, confirmed as spondylodiscitis from magnetic resonance imaging, a less common presentation of S. suis infection. After 4-week intravenous ceftriaxone treatment, he improved significantly with only hearing impairment remaining. CONCLUSION: Meningitis suis is a systemic infection which can manifest in any organ. The clinician should suspect any low back pain as spondylodiscitis in a patient who had S. suis meningitis.